A Coupled Reservoir Simulation-geomechanical Modelling Study of the CO2 Injection-induced Ground Surface Uplift Observed at Krechba, in Salah - Shi,J; Smith,J; Durucan,S; Korre,A (Energy Procedia, 2013)
Building on the previous reservoir simulation study of CO2 injection at Krechba, a coupled reservoir simulation- geomechanical modelling study was carried out, aiming to match the InSAR surface uplift time series at the three injection wells (KB-501, KB-502 and KB-503) over a 5-year injection period (August 2004 - October 2009). The geomechanical response at the ground surface to subsurface CO2 injection has been largely reproduced at KB-501; however mixed results were obtained for areas around KB-502 and KB-503. This work suggests that CO2 has most likely migrated up to the lower caprock around KB-502 from February/March 2006.